Variation in chemical composition and antimalarial activities of two samples of Terminalia albida collected from separate sites in Guinea - Camara, Aissata (BMC Complement Med Ther, 2021)
BACKGROUND: The disparity of harvesting locations can influence the chemical composition of a plant species, which could affect its quality and bioactivity. Terminalia albida is widely used in traditional Guinean medicine whose activity against malaria has been validated in vitro and in murine models. The present work investigated the antimalarial properties and chemical composition of two samples of T. albida collected from different locations in Guinea. METHOD: T. albida samples were collected in different locations in Guinea, in Dubréka prefecture (West maritime Guinea) and in Kankan prefecture (eastern Guinea). The identity of the samples was confirmed by molecular analysis. In vitro antiplasmodial activity of the two extracts was determined against the chloroquine resistant strain PfK1. In vivo, extracts (100 mg/kg) were tested in two experimental murine models, respectively infected with P. chabaudi chabaudi and P. berghei ANKA. The chemical composition of the two samples was assessed by ultra-high-performance liquid chromatography coupled to high resolution mass spectrometry. RESULTS: In vitro, the Dubréka sample (TaD) was more active with an IC(50) of 1.5 μg/mL versus 8.5 μg/mL for the extract from Kankan (TaK). In vivo, the antiparasitic effect of TaD was substantial with 56% of parasite inhibition at Day 10 post-infection in P. chabaudi infection and 61% at Day 8 in P. berghei model, compared to 14 and 19% inhibition respectively for the treatment with TaK. In addition, treatment with TaD further improved the survival of P. berghei infected-mice by 50% at Day 20, while the mortality rate of mice treated with Tak was similar to the untreated group. The LC/MS analysis of the two extracts identified 38 compounds, 15 of which were common to both samples while 9 and 14 other compounds were unique to TaD and TaK respectively. CONCLUSION: This study highlights the variability in the chemical composition of the species T. albida when collected in different geographical locations. These chemical disparities were associated with variable antimalarial effects. From a public health perspective, these results underline the importance of defining chemical fingerprints related to botanical species identification and to biological activity, for the plants most commonly used in traditional medicine. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12906-021-03231-3.